Apakah Repurchase Intention dapat Ditingkatkan melalui Digital Customer Experience? (Studi pada Konsumen Volcano Steak di GrabFood) - Ihda Farhatun Nisak (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2022)
The purpose of this study is to analyze the effect of digital customer experience on repurchase intention. The data from this study were obtained from 103 respondents who had purchased volcano steak food and drinks more than 2 times and used the Grab application, the analysis used in this study was a simple regression analysis that was previously tested through validity and reliability tests. The results of the significance level of 0.000 0.05, so the results of this study obtained that there was a significant influence between digital customer experience on repurchase intention of Volcano Steak customers. The variables analyzed in this study are quite important variables so that they are expected to be implemented to improve the experience and repeat returns made by Volcano steak consumers.